Green Products on Investment Market - Example of Socially Responsible Investment Funds - Ciechelska, Agnieszka ("Zielone" produkty na rynku inwestycyjnym na przykładzie społecznie odpowiedzialnych funduszy inwestycyjnych, 2009)
Since the 70s a new trend can be observed in financial decisions made by investors. Investors have been interested not only in the rate of return from invested capital but also resulting from their investments non-financial effects. There is not one and uniformed definition of investment funds which take into account non-financial issues in their investing strategies. They are currently defined as 'socially responsible investments' investment philosophy which matches non-financial goals (ethical, social and/or environmental) with financial goals. The main distinguishing mark is portfolio's construction which takes into consideration both, financial and non-financial goals.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 81, s. 9-23
Keywords: sustainable development; "green" funds; secially responsible funds